(N|TIMOLOGI^ESKIE OSNOWY SLOWARNOGO SOSTAWA SOWREMENNOGO ANGLIJSKOGO QZYKA (B/s - (NaMOSOWA(B, (Nn(B.(Nn(B.s ((NmOSKWA (B:s (NiNOSTRANNOJ LITERATURY (B,s, 1956)
(NbIBLIOGR(B.: (NS(B. 217-218s
Keywords: (NrUSSKIJ QZYK (B- (NlEKSIKAs